Penggunaan media tali andha aksara jawa untuk meningkatkan keterampilan menulis aksara jawa - Rani Aryawati; Hadi Mulyono; Joko Daryanto (Universitas Sebelas Maret, 2021)
This research aims to improve Javanese script writing skills for four grade students of Ta’mirul Islam Surakarta Elementary School in 2018/2019 academic year by using Tali Andha Aksara Jawa media. This Classroom Action Research consisted of two cyles with two learning in each cycle. Subject in this research were students and teacher in IV E grade of Ta’mirul Islam Surakarta Elementary School. Research data collection by way of interviews, observations, test, and document analysis. Source triangulation and technical triangulation used for data validity. The data in this research used descriptive comparative analysis techniques and interactive analysis model by Miles and Huberman. Classical completeness of students in initial condition was 8%, in first cycle showed 56%. then in second cycle showed 92%.Keywords: Writing skills, Javanese script, Tali Andha Aksara Jawa, elementary school